The Role of Carbohydrate in Maintaining Extensin in an Extended Conformation - Stafstrom, Joel P. (1986)
Monomers of the plant cell wall glycoprotein extensin are secreted into the wall where they become cross-linked to each other to form a rigid matrix. Expression of the extensin matrix is correlated with the inhibition of further cell elongation during normal development, with increased resistance to virulent pathogens and with other physiological responses characterized by wall strengthening. Carbohydrates make up about two-thirds of the mass of extensin. Arabinose oligomers linked to hydroxyproline residues represent 95% of the total carbohydrate with the remainder occurring as single residues of galactose linked to some serine residues. Electron microscopy of shadowed extensin shows the glycosylated form to be an easily visualized and highly elongated molecule. In contrast, extensin that has been deglycosylated with anhydrous hydrogen fluoride is difficult to resolve in the EM. Glycosylated extensin elutes from a gel filtration column much more rapidly than does the deglycosylated form, and from this analysis we have calculated respective Stokes' radii of 89 and 11 Ångstroms for these molecules. Others have shown that inhibition of extensin glycosylation has no effect on its secretion or insolubilization in the cell wall, but that this extensin cannot inhibit cell elongation. It is likely that carbohydrate moieties keep extensin in an extended conformation and that extensin must be in this conformation to form a cross-linked matrix that can function properly in vivo.